Delayed dark adaptation in central serous chorioretinopathy - Nigalye, Archana (Am J Ophthalmol Case Rep, 2021)
PURPOSE: To evaluate the effect of central serous chorioretinopathy (CSCR) on retinal function using dark adaptation in a human subject, and to follow it through resolution of the disease. PATIENTS: Single patient, 50 years old male patient, with acute CSCR in one eye and resolved old CSCR in the other eye. OBSERVATIONS: Observational study in patient with CSCR followed through resolution of the subretinal fluid (52 days). Dark adaptation was assessed using the AdaptDx® (Maculogix Inc.) measured by Rod Intercept time (RIT) in minutes. A normal retinal locus of the same eye on the opposite side of the fovea was used as control. Retinal separation (microns) was measured using Spectralis Optical Coherence Tomography (Spectralis®, HRA + OCT, Heidelberg engineering). Change in time to dark adapt, were correlated with retinal separation measured in microns, during the course of CSCR. The Rod Intercept time was delayed in the area of detached retina compared to the normal region (control) on presentation with retinal separation (RS) of 104 μm. The Rod Intercept time returned to normal as the retinal separation from retinal pigment epithelium decreased and eventually resolved. CONCLUSIONS: This case shows that delay in dark adaptation is proportional to the amount of separation of neurosensory retina from retinal pigment epithelium in CSCR, this may offer a potential of using DA to characterize visual function in CSCR. The association of dark adaptation response with the state of retinal pigment epithelial function and its ability to predict the recurrence of CSCR needs further evaluation.